Panel Autoregressive Distributed Lag Model in Analyzing the Impact of Macroeconomic Variables on Economic Growth in Sub-Saharan African Countries - Haruna , Alilu; M.O , Adenomon; Maijama’a, Bilkisu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study used a panel ARDL model to analyze the impact of macroeconomic variables on GDP in SSA countries over 33 years (1990 to 2021). It aimed to fit a panel ARDL model for these variables, estimate their long-run impact on GDP, and identify short-run effects. The analysis employed econometric techniques such as panel unit root tests, cointegration analysis, and model estimation. Findings suggested that in the long run, inflation, interest rates, and unemployment had no significant impact on economic growth, while exchange rates negatively affected GDP and export rates positively influenced it. On the hand, the ECT of (-1) indicated that the short run error would attain equilibrium at the speed of 16% annually. Inflation rate, interest rate, unemployment rate and export rate have no significant impact on GDP. However, exchange rate has a negative significant impact on economic growth on the short-run. The study therefore, recommended among others that pursuing trade liberalization policies that reduce barriers to international trade can promote export growth. Removing tariffs, simplifying customs procedures, and addressing non-tariff barriers can enhance the competitiveness of SSA countries in the global market. .